PENDAPATAN ASLI DAERAH DALAM PEMBIAYAAN PENGELUARAN RUTIN DAERAH KABUPATEN KULON PROGO (1990/91_1999/2000) - Udjianto, Didit W. (Jurnal Ekonomi & Studi Pembangunan, 2003)
The role of regional own revenues (Pendapatan Asli Daerah/PAD) in total budget of Pemda Kulon Progo decrease from 199 0 to 2000. This article analyzes especially on term efficiency in collecting region taxes.